IRF-3, IRF-5, and IRF-7 coordinately regulate the type I IFN response in myeloid dendritic cells downstream of MAVS signaling. - Helen M Lazear; Alissa Lancaster; Courtney Wilkins; Mehul S Suthar; Albert Huang; Sarah C Vick; Lisa Clepper; Larissa Thackray; Margaret M Brassil; Herbert W Virgin; Janko Nikolich-Zugich; Ashlee V Moses; et al. (PLoS Pathogens)
Although the transcription factors IRF-3 and IRF-7 are considered master regulators of type I interferon (IFN) induction and IFN stimulated gene (ISG) expression, Irf3(-/-)×Irf7(-/-) double knockout (DKO) myeloid dendritic cells (mDC) produce relatively normal levels of IFN-β after viral infection. We generated Irf3(-/-)×Irf5(-/-)×Irf7(-/-) triple knockout (TKO) mice to test whether IRF-5 was the source of the residual induction of IFN-β and ISGs in mDCs. In pathogenesis studies with two unrelated positive-sense RNA viruses (West Nile virus (WNV) and murine norovirus), TKO mice succumbed at rates greater than DKO mice and equal to or approaching those of mice lacking the type I IFN receptor (Ifnar(-/-)). In ex vivo studies, after WNV infection or exposure to Toll-like receptor agonists, TKO mDCs failed to produce IFN-β or express ISGs. In contrast, this response was sustained in TKO macrophages following WNV infection. To define IRF-regulated gene signatures, we performed microarray analysis on WNV-infected mDC from wild type (WT), DKO, TKO, or Ifnar(-/-) mice, as well as from mice lacking the RIG-I like receptor adaptor protein MAVS. Whereas the gene induction pattern in DKO mDC was similar to WT cells, remarkably, almost no ISG induction was detected in TKO or Mavs(-/-) mDC. The relative equivalence of TKO and Mavs(-/-) responses suggested that MAVS dominantly regulates ISG induction in mDC. Moreover, we showed that MAVS-dependent induction of ISGs can occur through an IRF-5-dependent yet IRF-3 and IRF-7-independent pathway. Our results establish IRF-3, -5, and -7 as the key transcription factors responsible for mediating the type I IFN and ISG response in mDC during WNV infection and suggest a novel signaling link between MAVS and IRF-5.